2003
DOI: 10.1046/j.1365-2133.2003.05475.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved risk-benefit ratio for topical triamcinolone acetonide in TransfersomeR in comparison with equipotent cream and ointment: a randomized controlled trial

Abstract: Transfersome may significantly improve the risk-benefit ratio of topically applied glucocorticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Regarding topical treatment, only transfersomes [99], antipsoriatic dithranol liposomes [46] and intraarticular clodronate liposomes for the treatment of RA [33] have entered the clinic. Regarding systemic treatment, it is mainly the work by Mizushima et al on lipid microspheres that has reached the clinic [100,101].…”
Section: Expert Opinionmentioning
confidence: 99%
“…Regarding topical treatment, only transfersomes [99], antipsoriatic dithranol liposomes [46] and intraarticular clodronate liposomes for the treatment of RA [33] have entered the clinic. Regarding systemic treatment, it is mainly the work by Mizushima et al on lipid microspheres that has reached the clinic [100,101].…”
Section: Expert Opinionmentioning
confidence: 99%
“…A clinical trial, involving triamcinolone acetonide formulated in second generation lipid vesicles (transferosomes) reported the vesicular formulation to be bioequivalent to commercial formulations (cream and ointment) containing a higher dose of the glucocorticoteroid (10% more). The findings of this study suggest that the use of transfersomoes may improve the risk-benefit ratio of topical glucocorticosteroids compared to conventional vehicles [60].…”
Section: Liposomesmentioning
confidence: 75%
“…In another study performed by Fesq et al [70], the efficacy of transfersomes was compared with commercially available cream and ointment formulations of TA in humans. According to the results of this study, 10-fold lower dose of TA in transfersome was found bioequivalent to conventional formulations as measured by erythema suppression.…”
Section: Formulations Of Tcmentioning
confidence: 99%